Housing and economic inequality in the long run: The retreat of owner occupation - Smith, Susan J; Clark, William A V; Vifotj, Rachel Ong; Wood, Gavin A; Lisowski, William; Truong, N T Khuong (My University, 2022)
Finally, after a lengthy hiatus, the empirical facts of economic inequality need no introduction. In a blaze of publicity during a decade or more, the re-polarization of income and wealth across nearly half a century has been widely documented and is substantially uncontested. There is debate on whether incomes have peaked, no doubt that capital is back, and a great deal of speculation on what might happen next. What is surprising is the limited attention afforded to the pivotal role of housing. To address that gap, conceptually and empirically, this paper draws from panel surveys in three countries across two decades to locate residential property generally, and owner-occupation in particular, within a wider literature on the shape of economic inequality in the long run.
Economy and Society
Keywords: Government, law and policy; Housing, communities and neighbourhoods; Income, wealth and finances